Exploring the Changes of Individual Risk Attitude in Cooperation Situations: An Experimental Study in China - Zhang, Pengsiman (2014)
This research aims at find the relationship between individual’s risk attitude and the cooperation situations. Two cooperation situations are identified in this research, namely risk ultimatum task and public risk task. An experiment was conducted in China. 62 subjects participated in the experiment. Risk attitude was measured by lottery choice with real stakes method which is presented by Eckel and Grossman (2008). The results indicate that risk attitude without cooperation is significantly related to risk attitude in cooperation situations. In risk ultimatum task, proposer acts more risk averse than in self task and this trend is more significant in risk-seeking subjects. The responders are likely to take risk which is far more risky than they chose in self task. In public risk task, when cooperate members do not know each other’s choice, they act much more risk loving than in self task. When subject know his choice will be told to his partner and his partner will make next choice according to is choice, the subject act more risk seeking than in self task but more risk averse than in the unknown treatment. When subject makes his decision after knowing his partner’s choice, he tends to balance the final risk to a middle level of risk.